Analisa Karakteristik Generator Sinkron Terhadap Perubahan Beban Daya Aktif - Ermawati, Ermawati; fadhli, fadhli; Machdalena, Machdalena; Harda Arya, Engla; Pernanda Lubis, Perdi (Fakultas Teknik UMRI, 2023)
Generators are electric machines that are used as generators of electrical energy, namely converting mechanical energy into electrical energy. Mechanical energy is obtained from the primover which can be a diesel engine, or something else. In large generators, conversion tools are often used, namely synchronous generators. so that the performance of the generator to be optimal it must be maintained stability. The purpose of this study is to examine and see the performance of synchronous generators against changes in active power load. From the analysis results, it is found that the lowest excitation current is 2.6 A, the reactive power is 1 MVAr, the highest excitation current is 6.08 A, the reactive power is 1.7 MVAr. When the excitation current is 6.08 A, the induced voltage is 16.12 kV. The Armature Current is 494.45 A, the Induction Voltage is 15.21 kV and the highest Armature Current value is 1,372.90 A with an Induction Voltage of 16.12 kV, the Induction voltage, the calculation results are 12.53 kV with an Active Power of 26 MW, the value of the Armature Current is 1,306 .62 A and the highest Induction Voltage is 16.54 kV, Active Power is 10 MW, Armature Current is 503.02 A